1996
DOI: 10.1577/1548-8667(1996)008<0028:esobcw>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Epizootiological Study of Bacterial Cold-Water Disease in Pacific Salmon and Further Characterization of the Etiologic Agent,Flexibacter psychrophila

Abstract: Isolates of Flexihacter psychrophila were obtained from chinook salmon Oncorhvnchus tshuwytscha and coho salmon O. kisntch that had previously sustained epizootics of coldwater disease. The pathogen was readily isolated from kidney and mucus of convalescent tish. The organisms were relatively inert in most standard microbiological media but were structurally and serologicalfy homogenous by examination of whole cell protein lysates by sodium dodecyl sulfate polyacrylamide gel clectrophoresis. In contrast to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 16 publications
0
20
0
1
Order By: Relevance
“…Different typing methods other than RAPD have been proposed to compare Flavobacterium psychrophilum strains among themselves: serologic analysis (Lorenzen 1994; genetic analysis based on plasmid profile (Holt 1987, Lorenzen 1994 or rRNA gene restriction pattern (ribotype) (Cipriano et al 1996); and electrophoretic pattern of proteases (Bertolini et al 1994). Although no association could be found between fish host and either ribotype or plasmid profile, some correlation between fish host and serotype did appear in the results published by Wakabayashi et al (1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different typing methods other than RAPD have been proposed to compare Flavobacterium psychrophilum strains among themselves: serologic analysis (Lorenzen 1994; genetic analysis based on plasmid profile (Holt 1987, Lorenzen 1994 or rRNA gene restriction pattern (ribotype) (Cipriano et al 1996); and electrophoretic pattern of proteases (Bertolini et al 1994). Although no association could be found between fish host and either ribotype or plasmid profile, some correlation between fish host and serotype did appear in the results published by Wakabayashi et al (1994).…”
Section: Discussionmentioning
confidence: 99%
“…Examples among fish-pathogenic bacteria include primers generating fingerprints which clearly differentiated Vibrio salmonicida, V. anguillarum, and V. fisheri (Martinez et al 1994) as well as different Aeromonas species isolated from fish (Miyata et al 1995) or from widely different clinical and environmental sources (Oakey et al 1996). Because very few template DNA and no previous knowledge of nucleotide sequence are required, and because the whole genome is analyzed (Oakey et al 1996), RAPD has several advantages over the other techniques that have been used alone or in various combinations for identifying Flavobactenum psychrophilun?, such a s phenotypical investigations (Holt 1987), DNA/DNA hybridization (Bernardet & Grirnont 1989), serological tests revealing specific antigens (Pacha 1968, Holt 1987, Cipriano et al 1996, wholecell protein (Bernardet et al 1996, Cipriano et al 1996 or fatty acid analyses (Bernardet et al 1996), a n d 1 6 s rDNA-targeted PCR (Toyama e t al. 1994).…”
Section: Identification Of F Psychrophilum With This Techniquementioning
confidence: 99%
“…Typing techniques, such as serotyping (Holt 1987, Lorenzen & Olesen 1997, Izumi & Wakabayashi 1999, Madetoja et al 2001 and ribosomal RNA gene restriction (ribotyping) analysis (Cipriano et al 1996, Madetoja et al 2001) have been used for the characterization and differentiation of Flavobacterium psychrophilum. A relationship between ribotypes and host fish species and between ribotype and serotype of F. psychrophilum has been suggested in previous studies , Madetoja et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The restriction ladders of the ribotype A (Cla I and Hae III) were identical with restriction patterns C1 (Cla I) and H1 (Hae III) previously reported by Madetoja et al (2001), who suggested a relationship between serotype Fd and genotype F1 (ribotype C1/H1/P1), which thus is confirmed by the present study. A possible relationship between antigenicity and ribotypes of F. psychrophilum isolates in previous studies has not been evaluated (Cipriano et al 1996). However, Madsen & Dalsgaard (2000 found that 75% of studied F. psychrophilum isolates belonged to a certain ribotype and serotype Th or Fd.…”
mentioning
confidence: 99%
“…. In the only previously published work dealing with the ribotyping of Flavobacterium psychrophilum isolates, 3 restriction endonucleases were tested on 4 strains retrieved from different hatcheries (Cipriano et al 1996). Each strain exhibited a different ribotype when EcoR I was used, suggesting that ribotyping could be used for studying the epidemiology of coldwater disease.…”
mentioning
confidence: 99%